(untitled) (Applied Biological Research, 2024)
The present studies were intended to expedite in vitro conservation of a threatened orchid Aerides multiflora through asymbiotic seed germination technique. The capsules were harvested at two different stages of development. The seeds were inoculated in Murashige and Skoog, 1962 (MS) medium as source of nutrition. The effect of PGRs [6-benzylaminopurine (BAP) @ 1 mg L-1 and auxin (α-naphthalene acetic acid; NAA @ 1 mg L-1) was also assessed individually and in combination for various morphogenetic events such as seed germination percentage, morphogenetic changes and seedling development which varied with the capsule stage. The seeds obtained from undehisced light- brown capsule germinated with better percentage as compared to seeds obtained from undehisced green capsule. Cent per cent seed germination was achieved in basal MS medium alone and BAP supplemented medium. Seedling with 2-3 leaves and 1-2 roots were formed with in 20.00 ± 0.20 weeks old cultures in basal medium. The growth of germinating entities remained arrested in NAA supplemented medium and resumed growth upon shift to ½ strength medium fortified with peptone (1 g L-1). BAP favoured multiplication of protocorms.